Immuno-histochemical features of the structure of foetuses’ uterus from the mothers with pregnancy complications - Kupriianova, Larisa (Journal of Education, Health and Sport, 2017)
Material of the research includes uterus of foetuses, that were dead on the gestational term between 21 and 41 weeks. According to peculiarities in the pregnancy course this material was divided into groups: foetuses from mothers with physiological pregnancy; foetuses from mothers. whose pregnancy takes its course on the background of the PE with different stages of the severity; and, finally, foetuses from mothers, whose pregnancy was complicated by the chronic infection of lower genital tracts. Research methods: macroscopic, histological, histochemical, immunohistochemical, morphometric, statistical. It was shown an excessive proliferation of the connective tissue in all structural components, in the composition of which prevails an immature collagen of the III type. It was also increased a production of the endothelin-1 by the vascular component of organs. In addition, it was defined an oppression of the functional activity of epithelial component by mucosa, which was expressed like decreasing of the hormonal activity of the the organ and increasing of the manifestation stage of apoptosis changes.